Quercus ilex recruitment in a drier world: A multi-stage demographic approach (Perspectives in Plant Ecology, Evolution and Systematics, 2013)
There is a growing interest in understanding and forecasting the responses of plant communities to projected changes of environmental conditions. Multi-stage demographic approaches, where plant recruitment is explored across multiple and consecutive stages, are essential to obtain a whole overview of the consequences of increasing aridity on tree recruitment and forest dynamics, but they are still rarely used. In this study, we present the results of an experimental rainfall exclusion aimed to evaluate the impact of projected increasing drought on multiple stage-specific probabilities of recruitment in a key tree species typical of late-successional Mediterranean woodlands (Quercus ilex L.). We calibrated linear and nonlinear likelihood models for the different demographic processes and calculated overall probabilities of recruitment along a wide range of microhabitat conditions. Rainfall exclusion altered Q. ilex recruitment throughout ontogeny. Seed maturation, seedling emergence and survival and, to a lesser extent, post-dispersal seed survival were the most sensitive demographic processes to decreased rainfall. Interestingly, both the identity of the most critical stages for recruitment and their specific sensitivity to rainfall manipulation depended largely on the yearly pattern of precipitation. The microhabitat heterogeneity strongly determined the success of recruitment in the study species. The experimental increase in drought displaced the peak of maximum overall recruitment towards the low end of the light gradient, suggesting that the dependence on shrubs for an effective recruitment in Q. ilex could be intensified under future environmental scenarios. In terms of phenotypic plasticity, Q. ilex seedlings responded more strongly to light availability than to experimentally increased drought, which could reduce its ability to persist under on-going environmental conditions due to climate change. Results from this study provide a full picture of the ecological and functional consequences of the projected rainfall reduction on tree recruitment and forest dynamics in two years of contrasting precipitation.

Leaf CO2 efflux is attenuated by acclimation of respiration to heat and drought in a Mediterranean tree (Functional Ecology, 2011)
* 1Understanding the effect of water deficit on plant respiration and its temperature sensitivity at long time-scales is important for anticipating the shift in ecosystem dynamics that is expected to occur as a result of climate change. * 2We investigated seasonal variations of leaf dark respiration and sensitivity to temperature in the upper and lower canopy of Quercus ilex trees in a forest stand that had been exposed to either 33% throughfall reduction or normal rainfall for the preceding 6 years. * 3For upper and lower canopy leaves, light-saturated photosynthesis and respiration at a reference temperature of 15 °C (R15) had the lowest values in late summer, when both traits were lower in trees subjected to throughfall reduction than in those subject to control conditions. Respiration acclimated to seasonal shifts in temperature, more intensively through summer than winter and in throughfall-exclusion than control trees. Foliar concentration of soluble sugars was positively correlated with R15 across seasons. * 4As leaf respiration decreased with increasing water deficit, and the relationship between water status and respiration did not differ between trees that had been exposed to 7 years of enhanced drought when compared with controls, we suggest that drier conditions projected for the Mediterranean may attenuate the stimulation of leaf respiratory CO2 release by global warming in Q. ilex forests.